Increased of IL-4 and Ig E Level in Infection Hookworm in Plantation Workers in Jember - Bagus Hermansyah; Yunita Armiyanti; Wiwien Sugih Utami (Faculty of Medicine, University of Jember, 2023)
Hookworm infection is a disease that is included in the neglected tropical disease. Hookworm infection is suffered by many plantation workers who are closely related to the soil in daily life. Immune response in hookworm-infected individuals will experience disorders, especially in eosinophilia, mastocytosis, and IgE stimulation. It is therefore important to know the immune response to hookworm infections in plantation workers. In this study, eosinophilia was calculated on peripheral blood smears and counts of IL-4 and Ig-E levels by ELISA. The results showed an increase in eosinophil levels from blood samples of patients and a significant increase in IL-4 and IgE levels based on the results of statistical analysis. Keywords: hookworm, plantation worker, IL-4, and IgE